The endothelial layer formation in the presence of AuNPs/CdSe/TaNPs-loaded PLCL/PVP-based electrospun nanofibers - Lasak, Magdalena; Nirwan, Viraj P.; Kuc-Ciepluch, Dorota; Tomasiuk, Ryszard; Chourpa, Igor; Fahmi, Amir; Ciepluch, Karol (Frontiers in Molecular Biosciences, 2025)
BackgroundElectrospun nanofibers, which are becoming increasingly popular in biomedicine, can directly or indirectly affect the properties and formation of the edothelial layer. This effect can be both toxic and pro-stimulatory. Therefore, in this study, electrospun nanofibers PLCL/PVP composed of biodegradable and biocompatible L-lactide-block-ϵ-caprolactone copolymer (PLCL, 70:30) blended with polyvinylpyrrolidone (PVP), containing in situ synthesized PVP different types of nanoparticles - gold (AuNPs), cadmium selenide (CdSe QDs) or tantalum (TaNPs), were investigated. Understanding how different modifications of nanofibers can affect the formation of the endothelial layer is crucial to using them as tools in tissue regeneration.Methodselectrospun nanofibers with gold (AuNPs), cadmium selenide (CdSe QDs) or tantalum (TaNPs), were synthesized and physico-chemical characteristic were caried out. Cytotoxicity and prostimulatory effect of nanofibers on Primary Human Umbilical Vein Endothelial Cells were tested by microscopic and spectrofluorescence techniques.ResultsThe endothelial layer forms to 75% confluence (after 24 h) and reaches 100% after 72 h when no nanofibers are present. A slower formation of the endothelial layer is seen in the presence of PLCL/PVP nanofibers (60%) and (80%) after 72 h. The introduction of various nanoparticles into the nanofibers caused changes in the morphology and rate of endothelial layer formation. In the presence of nanofibers modified with AuNPs after 72 h it reached only 40%. A similar effect was obtained for PLCL/PVP-CdSe QDs. In the case of PLCL/PVP-TaNPs, after 48 h 90% and after 72 h 100%. The tested nanofibers did not show toxic behavior towards the formed HUVEC cell monolayer. All of the tested nanofibers, except PLCL/PVP-TaNPs, induced increased HUVEC cells layer permeability, which resulted in increased translocation of fluorescently labeled dextran from 20% to 50%.ConclusionIt was estimated that the effect of nanofibers on the formation of the endothelial layer can be direct, where cells contact the nanofibers and thus the growth of the endothelium is hindered. Additionally, the uptake of biological fluid components can have an indirect effect on endothelial cells, their adhesion and growth. Among the tested nanofibers, non-toxic PLCL/PVP-TaNPs seem to be particularly promising due to safety issues and the possibility of using them as effective scaffolds.